ON INFORMATION COMPETENCE OF A MEDICAL STUDENT - Sergey A. Chernyad'yev; Marina A. Ufimtseva; Yuriy M. Bochkarev; Alla V. Getmanova (Moscow Polytechnic University, 2016)
The article accentuates the importance of information competence in medical student training. The authors consider the ability to search for an the expert knowledge, to analyze, select, sort and process the information obtained from outside sources via the Internet to be one of the necessary skills to assimilate into the professional environment. The paper presents the experience of the Ural State Medical University on the formation of information competence of medical students, including the use of electronic textbooks.